Industrial diversification in Zambia - Young, Alistair (New York : Praeger, 1973)
This book is a study of the manufacturing sector of the Zambian economy. Apart from examining the performance of this sector since independence, the book also focused on its colonial antecedents. According to the author the economic order prior to independence had a major bearing on its development after independence, and especially on the policy choices made by the Zambian government in attempting to promote its growth and diversification. At independence, the government faced -an economy largely integrated into the markets of southern Africa. After independence, Zambia began to shift out of the orbit of the southern Africa markets; and because of this, domestic investments were made in the manufacturing of products that hitherto had been undercut by foreign competition.
Includes bibliographical references: p. 322-328.
lje 19/02/2018
Loans
Keywords: Manufacturing industries; Diversification in industry; Industrial policy